The Evaluation of Business Incubator Program in Order to Create Entrepreneurial Students in Indonesia - Citra Marcella Nazira; Lindawati Kartika (International Journal of Management and Business Applied, 2022)
Purpose – This paper seeks to analyze the implementation and evaluate the effectiveness of the 2nd batch of Bright Cube programs. Methodology/approach – A survei from 246 participants of Bright Cube 2nd batch program. This research method includes a descriptive analysis, gap analysis, Return on Training Investment (ROTI) analysis, nad Net Promoter Score (NPS). Primary data in the form of questionnaires and secondary data in the form of literature studies. Findings – It was found that the implementation of the program has referred to the main performance indicators of MBKM. At the reaction level, participants' perceptions of the program were high. At the learning level, it has reached the online marketing design competency unit. At the behavioral level, participants are interested in becoming entrepreneurs. At the outcome level, the majority of participants recommended the program. ROTI result is positive. Improvements are needed regarding funding, program schedules, and intensity of activities. Therefore, this program has been running effectively. Novelty/value – As creating entrepreneurs is a solution to overcome the high unemployment rate in Indonesia. Bright Cube as one of entrepreneurial incubators, which is organized by the Management Department of IPB University, has integrated all stakeholders and part of MBKM (Merdeka Belajar-Kampus Merdeka).